High-strength bio-based textile fabric and method of making the same
Patent Information
- Application Number
- CN202610877270.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明要解决的技术问题,在于提供一种高强度生物基纺织面料及其制备方法,其通过将植物染料预先负载于植物多酚-植酸酯协同改性的纤维素增强组分上,使植物染料随该增强组分共同进入生物基PA56成纤基体中,有效解决了植物染料直接加入时在基体中分散不均和迁移的技术问题,同时赋予了面料良好的力学性能和染色牢度
1、本发明通过将植物染料预先负载于植物多酚-植酸酯协同改性的纤维素增强组分上,再与生物基PA56进行熔融混炼和熔融纺丝,使植物染料随改性纤维素增强组分共同进入生物基PA56成纤基体中,从而减少植物染料直接加入时的分散不均和迁移情况,即可以有效避免了染料分子在高温熔体中的无序扩散和团聚,显著减少了分散不均和迁移现象,提高了着色均匀性和色牢度。
Smart Images

Figure CN122879848A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bio-based textile materials technology, specifically to a high-strength bio-based textile fabric and its preparation method. Background Technology
[0002] Bio-based textiles are textile materials made from bio-based polymers, bio-based fibers, or naturally derived functional components. With the increasing demand for green processing of textile materials, incorporating natural components such as plant dyes and cellulose into the bio-based PA56 textile system has become a technological direction in the preparation of bio-based textile materials.
[0003] Existing bio-based PA56 textile fabrics are typically prepared using melt spinning, which involves drying bio-based PA56 chips, melting and extruding them, then spinning, cooling, oiling, drawing, and winding to obtain fibers, which are then woven or knitted to form the fabric. For fabric coloring, conventional methods include finishing dyeing and solution dyeing. Finishing dyeing generally involves applying dye to or incorporating the dye into the fiber after it has been formed, through a dye bath treatment; solution dyeing involves adding the coloring component to the polymer system before melt spinning, allowing the coloring component to co-form the fiber with the polymer melt.
[0004] However, in the process of realizing the technical solution of this application, the inventors of this application discovered that the above-mentioned technology has at least the following technical problems: when plant dyes are directly added to the bio-based PA56 melt spinning system, there is a lack of a stable pre-fixed carrier between the plant dyes and the bio-based PA56 fiber matrix, which makes it easy for the plant dyes to be unevenly dispersed and migrated during the melt mixing and spinning process. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a high-strength bio-based textile fabric and its preparation method. By preloading plant dyes onto a cellulose reinforcing component that is synergistically modified with plant polyphenols and phytates, the plant dyes enter the bio-based PA56 fiber matrix together with the reinforcing component. This effectively solves the technical problems of uneven dispersion and migration of plant dyes in the matrix when they are directly added, and at the same time endows the fabric with good mechanical properties and color fastness.
[0006] This invention is implemented as follows: A high-strength bio-based textile fabric, wherein the high-strength bio-based textile fabric is obtained by weaving or knitting high-strength bio-based composite fibers; the high-strength bio-based composite fibers are prepared from the following raw materials by weight: 100 parts of bio-based PA56, 6-22 parts of modified cellulose reinforcing component loaded with plant dyes, 2-6 parts of bio-based compatibilizer, 0.3-1.5 parts of heat-stabilizing processing aid, and 0.2-1 parts of lubricating and dispersing aid; The modified cellulose reinforcing component loaded with plant dye is a component formed by loading plant dye onto a plant polyphenol-phytate synergistic modified cellulose reinforcing component, wherein the mass ratio of the plant polyphenol-phytate synergistic modified cellulose reinforcing component to the plant dye is 100:2-100:25. The plant polyphenol-phytate synergistic modified cellulose reinforcing component is prepared from cellulose, phytate interface modifier and plant polyphenols. The amount of phytate interface modifier added is 5%-35% of the mass of cellulose, and the amount of plant polyphenols added is 3%-25% of the mass of cellulose. The phytate interface modifier is prepared by esterification reaction of phytic acid and polyethylene glycol monomethyl ether, wherein the molar ratio of phytic acid to polyethylene glycol monomethyl ether is 1:1 to 1:4.
[0007] Further, the relative viscosity of the bio-based PA56 is 2.3-2.8; the cellulose is one or more of bacterial cellulose, microfibrillated cellulose, regenerated cellulose powder, or chopped regenerated cellulose fibers; when the cellulose is in powder form, the particle size of the plant polyphenol-phytate synergistic modified cellulose reinforcing component is 1-80 μm; when the cellulose is chopped regenerated cellulose fiber, the length of the chopped regenerated cellulose fiber is 50-800 μm, and the aspect ratio is 5-50.
[0008] Furthermore, the plant polyphenols are one or more of tannic acid, gallic acid, tea polyphenols, or catechins; the plant dyes are one or more of madder dye, turmeric dye, indigo dye, gall dye, gardenia yellow dye, or sappanwood dye. The modified cellulose reinforcing component loaded with plant dyes is obtained by adsorption treatment, separation and drying of the plant polyphenol-phytate synergistic modified cellulose reinforcing component in a plant dye solution.
[0009] Furthermore, the bio-based compatibilizer is one or more of maleic anhydride-grafted bio-based polyamide, maleic anhydride-grafted polyolefin, or epoxy-modified polyamide elastomer; the heat-stabilizing processing aid is one or more of hindered phenolic antioxidants, phosphite antioxidants, or phosphate ester heat stabilizers; and the lubricating and dispersing aid is one or more of stearate, polyethylene wax, amide wax, or bio-based fatty acid ester.
[0010] Furthermore, the method for preparing the high-strength bio-based textile fabric includes the following steps: S1. Phytic acid, polyethylene glycol monomethyl ether, and catalyst are subjected to an esterification reaction under nitrogen protection to obtain a phytic acid ester interface modifier; wherein the molar ratio of phytic acid to polyethylene glycol monomethyl ether is 1:1-1:4, the amount of catalyst is 0.2%-2.0% of the total mass of phytic acid and polyethylene glycol monomethyl ether, the esterification reaction temperature is 80-125℃, and the esterification reaction time is 2-8h; S2. Disperse cellulose in a water-ethanol mixed solvent to obtain a cellulose dispersion; add the phytate interface modifier and plant polyphenols to the cellulose dispersion, react at 50-90℃ for 2-6 hours, and after filtration, washing, drying, pulverizing and sieving, obtain the plant polyphenol-phytate synergistic modified cellulose reinforcing component; wherein, the amount of phytate interface modifier added is 5%-35% of the cellulose mass, and the amount of plant polyphenols added is 3%-25% of the cellulose mass; S3. The plant polyphenol-phytate synergistic modified cellulose reinforcing component is added to the plant dye solution and adsorbed at 40-85℃ for 1-5 hours. After separation, washing and drying, the modified cellulose reinforcing component loaded with plant dye is obtained. The mass ratio of the plant polyphenol-phytate synergistic modified cellulose reinforcing component to the plant dye is 100:2-100:25. S4. Weigh out 100 parts of bio-based PA56, 6-22 parts of the modified cellulose reinforcing component loaded with the plant dye, 2-6 parts of bio-based compatibilizer, 0.3-1.5 parts of heat-stabilizing processing aid, and 0.2-1 parts of lubricating and dispersing aid according to the following mass percentages: premix the bio-based PA56, bio-based compatibilizer, heat-stabilizing processing aid, and lubricating and dispersing aid to obtain a premix. S5. The premixed material is added through the main feed port of the twin-screw extruder, and the modified cellulose reinforcing component loaded with plant dye is added through the side feed port of the twin-screw extruder. After melt mixing, extrusion, cooling, and pelleting, high-strength bio-based PA56 composite chips are obtained. The temperature of the twin-screw extruder is 230-275℃, and the screw speed is 120-300r / min. S6. The high-strength bio-based PA56 composite chips are melt-spun to obtain high-strength bio-based composite fibers; wherein the spinning temperature is 260-285℃ and the total draw ratio is 2.5-4.5 times. S7. The high-strength bio-based composite fiber is woven or knitted and then heat-set to obtain a high-strength bio-based textile fabric; wherein the heat-setting temperature is 120-180℃ and the heat-setting time is 20-120s.
[0011] Further, in step S1, the number average molecular weight of the polyethylene glycol monomethyl ether is 400-5000; the catalyst is one or more of p-toluenesulfonic acid, citric acid, tartaric acid or phosphotungstic acid; the esterification reaction is carried out under a stirring speed of 200-600 r / min, and the water generated in the reaction is removed by depressurization or nitrogen purging.
[0012] Further, in step S2, the volume ratio of water to ethanol in the water-ethanol mixed solvent is 90:10-40:60; the mass concentration of cellulose in the cellulose dispersion is 1%-12%; before adding the phytate interface regulator, the cellulose dispersion is pre-dispersed at 40-70℃ for 20-90 min; after adding the plant polyphenols, the pH of the system is adjusted to 3.5-6.5.
[0013] Further, in step S3, the mass concentration of the plant dye solution is 0.5%-8%, and the pH is 4.0-7.0; when the plant dye is a poorly soluble plant dye, an auxiliary solvent is added to the plant dye solution, and the auxiliary solvent is one or more of ethanol, glycerol or ethyl lactate, and the amount of auxiliary solvent is 5%-40% of the total mass of the plant dye solution.
[0014] Furthermore, in step S4, the premixing temperature is 25-60℃, the premixing speed is 300-1200 r / min, and the premixing time is 5-20 min; In step S5, the length-to-diameter ratio of the twin-screw extruder is 36:1-52:1, and the vacuum degree of the vacuum exhaust section is -0.04MPa to -0.09MPa; the high-strength bio-based PA56 composite chips are dried at 80-105℃ for 4-10h before melt spinning.
[0015] Further, in step S6, the spinneret aperture of the melt spinning process is 0.15-0.45 mm, and the number of spinneret holes is 24-144. After the melt is extruded through the spinneret, it is cooled by side blowing air, with a side blowing air temperature of 18-28℃, a side blowing air relative humidity of 55%-80%, and a side blowing air velocity of 0.25-0.80 m / s. The high-strength bio-based composite fiber is bundled, oiled, stretched, heat-set, and wound, with an oiling rate of 0.3%-1.2%, a heat-setting roller temperature of 120-170℃, and a winding speed of 800-3500 m / min.
[0016] The present invention has the following advantages: 1. This invention preloads plant dyes onto a cellulose reinforcing component that has been synergistically modified with plant polyphenols and phytates, and then melt-blends and melt-spun it with bio-based PA56. This allows the plant dyes to enter the bio-based PA56 fiber matrix along with the modified cellulose reinforcing component, thereby reducing the uneven dispersion and migration when the plant dyes are directly added. This effectively avoids the disorderly diffusion and aggregation of dye molecules in the high-temperature melt, significantly reduces uneven dispersion and migration, and improves color uniformity and color fastness.
[0017] 2. This invention synergistically modifies cellulose using phytate interface modifiers and plant polyphenols, introducing flexible polyether segments and reactive polyphenol groups with good compatibility with PA56 onto the cellulose surface. The polyether segments in the phytate have good compatibility with the PA56 matrix, while the polyphenol groups can form hydrogen bonds and other interactions with the matrix. Together, they reduce the interfacial tension between cellulose and PA56, enhance interfacial bonding, and reduce interfacial separation, thereby improving the mechanical strength of the composite fiber.
[0018] 3. This invention employs a step-by-step feeding process using main and side feed ports. Specifically, the PA56 matrix, bio-based compatibilizer, heat-stabilizing processing aid, and lubricating and dispersing aid are premixed and added through the main feed port. Meanwhile, the fibrous or powdered plant dye-loaded modified cellulose reinforcing component is added through the side feed port. This process better maintains the structural integrity of the cellulose reinforcing component, reduces excessive shearing and thermal degradation in the screw, ensures its uniform dispersion in the matrix, and improves the continuity and stability of the composite chip preparation and spinning process.
[0019] In summary, the high-strength bio-based textile fabric prepared by this invention has the characteristics of high strength, excellent color fastness and full bio-based properties. The preparation method is stable, easy to operate and easy to realize industrial production. Attached Figure Description
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0021] Figure 1 This is a flowchart of a method for preparing a high-strength bio-based textile fabric according to the present invention. Detailed Implementation
[0022] The following will be combined with the appendix Figure 1 The technical solution of the present invention will be clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0023] Preparation Example 1: Preparation of Phytate Interface Modifier A Weigh 37.7g of a 70% phytic acid aqueous solution, of which 26.4g is effective phytic acid, corresponding to 0.04mol of phytic acid; weigh 80.0g of polyethylene glycol monomethyl ether with a number average molecular weight of 1000, corresponding to 0.08mol of polyethylene glycol monomethyl ether; weigh 1.06g of citric acid as a catalyst.
[0024] A phytic acid aqueous solution was added to a four-necked reaction flask equipped with a mechanical stirrer, thermometer, nitrogen inlet tube, and pressure reducing port. The mixture was heated to 80°C with a stirring speed of 300 rpm and treated under a vacuum of -0.085 MPa for 60 min to remove some of the moisture. The pressure was then released, and polyethylene glycol monomethyl ether and citric acid were added to the reaction flask. Nitrogen gas was then purged into the flask to replace the gas inside for 15 min. After purging, the reaction system was heated to 105°C, the stirring speed was adjusted to 400 rpm, and the reaction was carried out for 5 h under nitrogen protection. During the reaction, the generated moisture was continuously purged with nitrogen.
[0025] After the reaction was completed, the reaction system was cooled to 50°C and treated under a vacuum of -0.085 MPa for 30 min to obtain a light yellow viscous liquid, which is phytate interface modifier A. The obtained phytate interface modifier A was directly used for subsequent cellulose surface treatment without single-compound separation.
[0026] Preparation Example 2: Preparation of Cellulose Reinforcing Component A Synergistically Modified by Plant Polyphenols and Phytates Weigh 50.0 g of dried bacterial cellulose powder and add it to a water-ethanol mixed solvent consisting of 1050 mL of deionized water and 450 mL of anhydrous ethanol to obtain a cellulose dispersion. Place the cellulose dispersion in a reaction vessel equipped with a mechanical stirrer and disperse it for 60 min at 60 °C and a stirring speed of 700 r / min.
[0027] After dispersion, 7.5 g of the phytate interface modifier A obtained in Preparation Example 1 was added to the cellulose dispersion, and the mixture was further treated at 60 °C and a stirring speed of 700 r / min for 60 min. Subsequently, 4.0 g of tannic acid was added, and the pH of the system was adjusted to 5.0 using a 5% sodium carbonate aqueous solution. The reaction temperature was then increased to 70 °C, and the reaction was carried out at a stirring speed of 700 r / min for 4 h.
[0028] After the reaction was completed, the reaction system was cooled to 35°C and filtered through a filter cloth to obtain a solid. The obtained solid was washed three times with deionized water and twice with anhydrous ethanol, with each wash using 500 mL of liquid. The washed solid was placed in a forced-air drying oven and dried at 65°C for 12 hours. After drying, the obtained solid was pulverized and sieved through a 200-mesh sieve to obtain plant polyphenol-phytate synergistic modified cellulose reinforcing component A.
[0029] Preparation Example 3: Preparation of Modified Cellulose Reinforcing Component A Loaded with Plant Dyes Weigh 5.0 g of madder dye and add it to a mixed solvent consisting of 200 mL of deionized water and 50 mL of anhydrous ethanol. Stir at 50 °C and 500 rpm for 30 min to obtain a madder dye solution. Adjust the pH of the madder dye solution to 5.5 using a 5% (w / w) citric acid aqueous solution.
[0030] Weigh 0.0 g of the plant polyphenol-phytate synergistic modified cellulose reinforcing component A1 obtained in Preparation Example 2 and add it to the above madder dye solution. Raise the system temperature to 60°C and perform adsorption treatment at a stirring speed of 600 r / min for 3 h. After the adsorption treatment, cool the system to 30°C and perform solid-liquid separation by centrifugation at a speed of 4000 r / min for 10 min.
[0031] The solid obtained from centrifugation was washed twice rapidly with 300 mL of deionized water each time. The washed solid was then placed in a forced-air drying oven and dried at 60°C for 10 hours to obtain plant dye-loaded modified cellulose reinforcing component A. This plant dye-loaded modified cellulose reinforcing component A was used for the subsequent preparation of high-strength bio-based PA56 composite slices. Example 1
[0032] S1. Preparation of phytate interface modifier: Same as in preparation example 1.
[0033] S2. Preparation of plant polyphenol-phytate synergistic modified cellulose reinforcing component: same as preparation example 2.
[0034] S3. Preparation of plant dye-loaded modified cellulose reinforcing component: Same as in preparation example 3, except that the amount of madder dye used is 2.0 g, which is added to a mixed solvent consisting of 160 mL of deionized water and 40 mL of anhydrous ethanol.
[0035] S4. Preparation of premix: Weigh 1000.0g of bio-based PA56 chips with a relative viscosity of 2.4, place them in a vacuum drying oven, and dry them for 8 hours at 95℃ and a vacuum degree of -0.085MPa. Weigh 30.0g of maleic anhydride-grafted bio-based polyamide, 5.0g of hindered phenolic antioxidant, and 3.0g of polyethylene wax.
[0036] The dried bio-based PA56 chips, maleic anhydride-grafted bio-based polyamide, hindered phenolic antioxidants and polyethylene wax were added to a high-speed mixer and premixed for 10 minutes at 40°C and 800 r / min to obtain premix A.
[0037] S5. Preparation of composite chips: Add premix A through the main feed port of the twin-screw extruder, and add 60.0g of the plant dye-loaded modified cellulose reinforcing component A obtained in step S3 through the side feed port.
[0038] The twin-screw extruder has a length-to-diameter ratio of 40:1, a screw speed of 180 r / min, and a vacuum level of -0.075 MPa in the vacuum exhaust section. The temperatures in zones 1, 2, 3, 4, and 5 of the twin-screw extruder are 235℃, 245℃, 255℃, 265℃, and 270℃, respectively, with a die head temperature of 270℃. The melt-blended material is extruded, water-cooled, and pelletized to obtain high-strength bio-based PA56 composite chips A.
[0039] S6. Melt spinning: High-strength bio-based PA56 composite chips A were placed in a vacuum drying oven and dried for 8 hours at 95℃ and a vacuum of -0.085MPa. The dried high-strength bio-based PA56 composite chips A were then added to a melt spinning apparatus for melt spinning. The spinning temperature was 275℃, the spinneret orifice diameter was 0.30mm, and the number of spinneret orifices was 72.
[0040] After the melt is extruded through a spinneret, it is cooled by side-blowing air at a temperature of 22°C, a relative humidity of 65%, and a wind speed of 0.45 m / s. The nascent fibers are then bundled, oiled, drawn, heat-set, and wound. The oiling rate is 0.6%, the temperature of the first drawing roll is 80°C, the temperature of the second drawing roll is 120°C, the temperature of the heat-setting roll is 150°C, the total draw ratio is 3.2, and the winding speed is 1800 m / min, yielding high-strength bio-based composite fiber A.
[0041] S7. Weaving and Finishing: High-strength bio-based composite fiber A is twisted to a twist of 300 twists / m. The twisted fiber is then warped and woven to form a grey fabric with a plain weave structure. The resulting grey fabric undergoes heat setting at 150℃ for 60 seconds. After heat setting, high-strength bio-based textile fabric A is obtained. Example 2
[0042] S1. Weigh 37.7g of a 70% phytic acid aqueous solution, of which the effective content of phytic acid is 26.4g, corresponding to 0.04mol of phytic acid; weigh 160.0g of polyethylene glycol monomethyl ether with a number average molecular weight of 2000, corresponding to 0.08mol of polyethylene glycol monomethyl ether; weigh 1.86g of tartaric acid as a catalyst.
[0043] A phytic acid aqueous solution was added to a four-necked reaction flask equipped with a mechanical stirrer, thermometer, nitrogen inlet tube, and pressure reducing port. The mixture was heated to 80°C with a stirring speed of 300 rpm and treated under a vacuum of -0.085 MPa for 60 min. The pressure was then released, and polyethylene glycol monomethyl ether and tartaric acid were added to the reaction flask. Nitrogen gas was then purged for 15 min. After purging, the reaction system was heated to 110°C, the stirring speed was adjusted to 450 rpm, and the reaction was carried out under nitrogen protection for 6 h. During the reaction, water generated was continuously removed by nitrogen purging. After the reaction, the reaction system was cooled to 50°C and treated under a vacuum of -0.085 MPa for 30 min to obtain phytate ester interface modifier B.
[0044] S2. Weigh 50.0 g of microfibrillated cellulose and add it to a water-ethanol mixed solvent consisting of 900 mL of deionized water and 600 mL of anhydrous ethanol to obtain a cellulose dispersion. Place the cellulose dispersion in a reaction vessel equipped with a mechanical stirrer and disperse it at 65 °C and a stirring speed of 800 r / min for 60 min.
[0045] After dispersion, 12.5 g of phytate interface regulator B was added to the cellulose dispersion, and the mixture was further treated at 65 °C and 800 r / min for 60 min. Subsequently, 3.0 g of gallic acid and 3.0 g of tea polyphenols were added, and the pH of the system was adjusted to 5.5 using a 5% sodium carbonate aqueous solution. The reaction temperature was then increased to 75 °C, and the reaction was carried out at 800 r / min for 4 h.
[0046] After the reaction was completed, the reaction system was cooled to 35°C and filtered through a filter cloth to obtain a solid. The obtained solid was washed three times with deionized water and twice with anhydrous ethanol, with each wash using 500 mL of liquid. The washed solid was placed in a forced-air drying oven and dried at 65°C for 12 hours. After drying, the obtained solid was pulverized and sieved through a 200-mesh sieve to obtain plant polyphenol-phytate synergistic modified cellulose reinforcing component B.
[0047] S3. Weigh 5.0 g of turmeric dye and 5.0 g of gardenia yellow dye, add them to a mixed solvent consisting of 300 mL of deionized water, 100 mL of anhydrous ethanol, and 50 mL of ethyl lactate, and stir for 40 min at 55 °C and 500 r / min to obtain a plant dye solution. Adjust the pH of the plant dye solution to 5.8 using a 5% (w / w) citric acid aqueous solution.
[0048] 100.0 g of plant polyphenol-phytate synergistic modified cellulose reinforcing component B was weighed and added to the above plant dye solution. The system temperature was raised to 65℃, and adsorption treatment was carried out for 3 h at a stirring speed of 650 r / min. After the adsorption treatment, the system was cooled to 30℃, and solid-liquid separation was performed by centrifugation at a speed of 4000 r / min for 10 min. The solid obtained by centrifugation was taken and washed twice with deionized water, with 300 mL of deionized water used each time. The washed solid was placed in a forced-air drying oven and dried at 60℃ for 10 h to obtain plant dye-loaded modified cellulose reinforcing component B.
[0049] S4. Preparation of premix: Weigh 1000.0g of bio-based PA56 chips with a relative viscosity of 2.5, place them in a vacuum drying oven, and dry them for 8 hours at 95℃ and a vacuum degree of -0.085MPa. Weigh 40.0g of maleic anhydride-grafted polyolefin, 8.0g of phosphite antioxidant, and 5.0g of amide wax.
[0050] The dried bio-based PA56 chips, maleic anhydride-grafted polyolefin, phosphite antioxidants and amide wax were added to a high-speed mixer and premixed for 12 minutes at 45°C and 900 r / min to obtain premix B.
[0051] S5. Preparation of composite chips: Weigh 140.0g of plant dye-loaded modified cellulose reinforcing component B. Add premix B through the main feed port of the twin-screw extruder, and add plant dye-loaded modified cellulose reinforcing component B through the side feed port of the twin-screw extruder.
[0052] The twin-screw extruder has a length-to-diameter ratio of 44:1, a screw speed of 200 r / min, and a vacuum level of -0.080 MPa in the vacuum exhaust section. The temperatures in zones 1, 245℃, 3, 255℃, 4, 265℃, and 5 (die head) of the twin-screw extruder are 270℃. The melt-blended material is extruded, water-cooled, and pelletized to obtain high-strength bio-based PA56 composite chips B.
[0053] S6. Melt spinning: High-strength bio-based PA56 composite chips B were placed in a vacuum drying oven and dried for 8 hours at 95℃ and a vacuum of -0.085MPa. The dried high-strength bio-based PA56 composite chips B were then added to a melt spinning apparatus for melt spinning. The spinning temperature was 278℃, the spinneret orifice diameter was 0.30mm, and the number of spinneret orifices was 72.
[0054] After the melt is extruded through a spinneret, it is cooled by side-blowing air at a temperature of 23°C, a relative humidity of 65%, and a wind speed of 0.50 m / s. The nascent fibers are then bundled, oiled, drawn, heat-set, and wound. The oiling rate is 0.7%, the temperature of the first drawing roller is 85°C, the temperature of the second drawing roller is 125°C, the temperature of the heat-setting roller is 155°C, the total draw ratio is 3.5, and the winding speed is 2000 m / min, yielding high-strength bio-based composite fiber B.
[0055] S7. Weaving and Finishing: High-strength bio-based composite fiber B is twisted to a twist of 320 twists / m. The twisted fiber is then warped and woven to form a greige fabric with a twill weave. The resulting greige fabric undergoes heat setting at 155℃ for 60 seconds. After heat setting, high-strength bio-based textile fabric B is obtained. Example 3
[0056] S1. Weigh 37.7g of a 70% phytic acid aqueous solution, of which the effective content of phytic acid is 26.4g, corresponding to 0.04mol of phytic acid; weigh 400.0g of polyethylene glycol monomethyl ether with a number average molecular weight of 5000, corresponding to 0.08mol of polyethylene glycol monomethyl ether; weigh 3.84g of p-toluenesulfonic acid as a catalyst.
[0057] A phytic acid aqueous solution was added to a four-necked reaction flask equipped with a mechanical stirrer, thermometer, nitrogen inlet tube, and pressure reducing port. The mixture was heated to 80°C with a stirring speed of 300 rpm and treated under a vacuum of -0.085 MPa for 60 min. The pressure was then released, and polyethylene glycol monomethyl ether and p-toluenesulfonic acid were added to the reaction flask. Nitrogen gas was then purged for 15 min. After purging, the reaction system was heated to 115°C, the stirring speed was adjusted to 500 rpm, and the reaction was carried out under nitrogen protection for 6 h. During the reaction, water generated was continuously removed by nitrogen purging. After the reaction, the reaction system was cooled to 50°C and treated under a vacuum of -0.085 MPa for 30 min to obtain phytic acid ester interface modifier C.
[0058] S2. Weigh 50.0 g of short-cut regenerated cellulose fibers with a length of 300 μm and an aspect ratio of 20, and add them to a water-ethanol mixed solvent consisting of 750 mL of deionized water and 750 mL of anhydrous ethanol to obtain a cellulose dispersion. Place the cellulose dispersion in a reaction vessel equipped with a mechanical stirrer and disperse it at 65 °C and a stirring speed of 900 r / min for 60 min.
[0059] After dispersion, 17.5 g of phytate interface modifier C was added to the cellulose dispersion, and the mixture was further treated at 65 °C and 900 r / min for 60 min. Subsequently, 12.5 g of tannic acid was added, and the pH of the system was adjusted to 6.0 using a 5% sodium carbonate aqueous solution. The reaction temperature was then increased to 80 °C, and the reaction was carried out at 900 r / min for 5 h.
[0060] After the reaction was completed, the reaction system was cooled to 35°C and filtered through a filter cloth to obtain a solid. The obtained solid was washed three times with deionized water and twice with anhydrous ethanol, with each wash using 500 mL of liquid. The washed solid was placed in a forced-air drying oven and dried at 70°C for 12 h to obtain the plant polyphenol-phytate synergistic modified cellulose reinforcing component C.
[0061] S3. Weigh 12.5g of indigo dye and 12.5g of gallic acid dye, add them to a mixed solvent consisting of 300mL of deionized water, 150mL of anhydrous ethanol, and 100mL of ethyl lactate, and stir for 60min at 60℃ and 600r / min to obtain a plant dye solution. Adjust the pH of the plant dye solution to 6.0 using a 5% (w / w) citric acid aqueous solution.
[0062] 100.0 g of the plant polyphenol-phytate synergistic modified cellulose reinforcing component C was weighed and added to the above plant dye solution. The system temperature was raised to 70℃, and adsorption treatment was carried out at a stirring speed of 700 r / min for 4 h. After the adsorption treatment, the system was cooled to 30℃, and solid-liquid separation was performed by centrifugation at a speed of 4000 r / min for 10 min. The solid obtained by centrifugation was taken and washed twice with deionized water, with 300 mL of deionized water used each time. The washed solid was placed in a forced-air drying oven and dried at 65℃ for 12 h to obtain the plant dye-loaded modified cellulose reinforcing component C.
[0063] S4. Preparation of premix: Weigh 1000.0g of bio-based PA56 chips with a relative viscosity of 2.6, place them in a vacuum drying oven, and dry them for 8 hours at 100℃ and a vacuum degree of -0.085MPa. Weigh 60.0g of epoxy-modified polyamide elastomer, 15.0g of phosphate ester heat stabilizer, and 10.0g of bio-based fatty acid ester.
[0064] The dried bio-based PA56 chips, epoxy-modified polyamide elastomer, phosphate ester heat stabilizer and bio-based fatty acid ester were added to a high-speed mixer and premixed for 15 min at 50°C and 1000 r / min to obtain premix C.
[0065] S5. Preparation of composite chips: Weigh 220.0g of plant dye-loaded modified cellulose reinforcing component C. Add the premix C through the main feed port of the twin-screw extruder, and add the plant dye-loaded modified cellulose reinforcing component C through the side feed port of the twin-screw extruder.
[0066] The twin-screw extruder has a length-to-diameter ratio of 48:1, a screw speed of 220 r / min, and a vacuum level of -0.085 MPa in the vacuum exhaust section. The temperatures in zones 1, 2, 260, 270, 275, and 275℃ are all controlled by the twin-screw extruder. The melt-blended material is extruded, water-cooled, and pelletized to obtain high-strength bio-based PA56 composite chips C.
[0067] S6. Melt spinning: High-strength bio-based PA56 composite chips C were placed in a vacuum drying oven and dried for 8 hours at 100℃ and a vacuum of -0.085MPa. The dried high-strength bio-based PA56 composite chips C were then added to a melt spinning apparatus for melt spinning. The spinning temperature was 282℃, the spinneret orifice diameter was 0.35mm, and the number of spinneret orifices was 96.
[0068] The melt is extruded through a spinneret and cooled by side-blowing air at a temperature of 24°C, a relative humidity of 70%, and a wind speed of 0.55 m / s. The nascent fibers are then bundled, oiled, drawn, heat-set, and wound. The oiling rate is 0.8%, the temperature of the first drawing roll is 85°C, the temperature of the second drawing roll is 130°C, the temperature of the heat-setting roll is 160°C, the total draw ratio is 3.8, and the winding speed is 2200 m / min, yielding high-strength bio-based composite fiber C.
[0069] S7. Weaving and Finishing: The high-strength bio-based composite fiber C is fed into a knitting machine to knit into fabric. The knitting structure is plain weft knit. The resulting fabric is then heat-set at 160℃ for 75 seconds. After heat setting, the high-strength bio-based textile fabric C is obtained. Example 4
[0070] S1. Weigh 37.7g of a 70% phytic acid aqueous solution, of which the effective content of phytic acid is 26.4g, corresponding to 0.04mol of phytic acid; weigh 16.0g of polyethylene glycol monomethyl ether with a number average molecular weight of 400, corresponding to 0.04mol of polyethylene glycol monomethyl ether; weigh 0.085g of citric acid as a catalyst.
[0071] A phytic acid aqueous solution was added to a four-necked reaction flask equipped with a mechanical stirrer, thermometer, nitrogen inlet tube, and pressure reducing port. The mixture was heated to 80°C with a stirring speed of 200 rpm and treated under a vacuum of -0.080 MPa for 60 min. The pressure was then released, and polyethylene glycol monomethyl ether and citric acid were added to the reaction flask. Nitrogen gas was then purged for 15 min. After purging, the reaction system was heated to 80°C, the stirring speed was adjusted to 200 rpm, and the reaction was carried out under nitrogen protection for 2 h. During the reaction, water generated was continuously removed by nitrogen purging. After the reaction, the reaction system was cooled to 50°C and treated under a vacuum of -0.080 MPa for 30 min to obtain phytate interface modifier D.
[0072] S2. Weigh 50.0 g of regenerated cellulose powder and add it to a water-ethanol mixed solvent consisting of 1350 mL of deionized water and 150 mL of anhydrous ethanol to obtain a cellulose dispersion. Place the cellulose dispersion in a reaction vessel equipped with a mechanical stirrer and disperse it for 20 min at 40 °C and a stirring speed of 300 r / min.
[0073] After dispersion, 2.5 g of phytate interface modifier D was added to the cellulose dispersion, and the mixture was further treated at 40 °C and 300 r / min for 30 min. Subsequently, 1.5 g of gallic acid was added, and the pH of the system was adjusted to 3.5 using a 5% citric acid aqueous solution and a 5% sodium carbonate aqueous solution. The reaction temperature was then increased to 50 °C, and the reaction was carried out at 300 r / min for 2 h.
[0074] After the reaction was completed, the reaction system was cooled to 35°C and filtered through a filter cloth to obtain a solid. The obtained solid was washed twice with deionized water and twice with anhydrous ethanol, with each wash using 500 mL of liquid. The washed solid was placed in a forced-air drying oven and dried at 55°C for 12 h. After drying, the obtained solid was pulverized and sieved through a 300-mesh sieve to obtain plant polyphenol-phytate synergistic modified cellulose reinforcing component D, with a particle size of 8-48 μm after sieving.
[0075] S3. Weigh 2.0 g of madder dye and add it to a mixed solvent consisting of 190 mL of deionized water and 10 mL of anhydrous ethanol. Stir at 40 °C and 200 r / min for 30 min to obtain a madder dye solution. Adjust the pH of the madder dye solution to 4.0 using a 5% (w / w) citric acid aqueous solution.
[0076] 100.0 g of plant polyphenol-phytate synergistic modified cellulose reinforcing component D was weighed and added to the above madder dye solution. The system temperature was controlled at 40℃, and adsorption treatment was carried out for 1 h at a stirring speed of 200 r / min. After the adsorption treatment, the system was cooled to 30℃, and solid-liquid separation was performed by centrifugation at a speed of 4000 r / min for 10 min. The solid obtained by centrifugation was taken and washed twice with deionized water, with 300 mL of deionized water used each time. The washed solid was placed in a forced-air drying oven and dried at 50℃ for 12 h to obtain plant dye-loaded modified cellulose reinforcing component D.
[0077] S4. Preparation of premix: Weigh 1000.0g of bio-based PA56 chips with a relative viscosity of 2.3, place them in a vacuum drying oven, and dry them for 8 hours at 90℃ and a vacuum degree of -0.080MPa. Weigh 20.0g of maleic anhydride-grafted bio-based polyamide, 3.0g of hindered phenolic antioxidant, and 2.0g of calcium stearate.
[0078] The dried bio-based PA56 chips, maleic anhydride-grafted bio-based polyamide, hindered phenolic antioxidants and calcium stearate were added to a high-speed mixer and premixed for 5 minutes at 25°C and 300 r / min to obtain premix D.
[0079] S5. Preparation of composite chips: Weigh 60.0g of plant dye-loaded modified cellulose reinforcing component D. Add the premix D through the main feed port of the twin-screw extruder, and add the plant dye-loaded modified cellulose reinforcing component D through the side feed port of the twin-screw extruder.
[0080] The twin-screw extruder has a length-to-diameter ratio of 36:1, a screw speed of 120 r / min, and a vacuum level of -0.040 MPa in the vacuum exhaust section. The temperatures in zones 1, 240℃, 3, 250℃, 4, 260℃, and 5, as well as the die head temperature, are 265℃. The melt-blended material is extruded, water-cooled, and pelletized to obtain high-strength bio-based PA56 composite chips (D).
[0081] S6. Melt spinning: High-strength bio-based PA56 composite chips D were placed in a vacuum drying oven and dried at 80℃ for 10 hours. The dried high-strength bio-based PA56 composite chips D were then added to a melt spinning apparatus for melt spinning. The spinning temperature was 260℃, the spinneret orifice diameter was 0.15mm, and the number of spinneret orifices was 24.
[0082] The melt is extruded through a spinneret and cooled by side-blowing air at a temperature of 18°C, a relative humidity of 55%, and a wind speed of 0.25 m / s. The nascent fibers are then bundled, oiled, drawn, heat-set, and wound. The oiling rate is 0.3%, the temperature of the first drawing roller is 60°C, the temperature of the second drawing roller is 90°C, the temperature of the heat-setting roller is 120°C, the total draw ratio is 2.5, and the winding speed is 800 m / min, yielding high-strength bio-based composite fiber D.
[0083] S7. Weaving and Finishing: The high-strength bio-based composite fiber D is twisted to a twist of 200 twists / m. The twisted fiber is then warped and woven to form a grey fabric with a plain weave structure. The resulting grey fabric undergoes heat setting at 120℃ for 120 seconds. After heat setting, the high-strength bio-based textile fabric D is obtained. Example 5
[0084] S1. Weigh 37.7g of a 70% phytic acid aqueous solution, of which the effective content of phytic acid is 26.4g, corresponding to 0.04mol of phytic acid; weigh 800.0g of polyethylene glycol monomethyl ether with a number average molecular weight of 5000, corresponding to 0.16mol of polyethylene glycol monomethyl ether; weigh 16.5g of phosphotungstic acid as a catalyst.
[0085] A phytic acid aqueous solution was added to a four-necked reaction flask equipped with a mechanical stirrer, thermometer, nitrogen inlet, and pressure reducing port. The mixture was heated to 80°C with a stirring speed of 600 rpm and treated under a vacuum of -0.090 MPa for 60 min. The pressure was then released, and polyethylene glycol monomethyl ether and phosphotungstic acid were added to the reaction flask. Nitrogen gas was then purged for 15 min. After purging, the reaction system was heated to 125°C, the stirring speed was adjusted to 600 rpm, and the reaction was carried out under nitrogen protection for 8 h. During the reaction, water generated was continuously removed by nitrogen purging. After the reaction, the reaction system was cooled to 50°C and treated under a vacuum of -0.090 MPa for 30 min to obtain phytic acid ester interface modifier E.
[0086] S2. Weigh 50.0 g of short-cut regenerated cellulose fibers with a length of 800 μm and an aspect ratio of 50, and add them to a water-ethanol mixed solvent consisting of 200 mL of deionized water and 300 mL of anhydrous ethanol to obtain a cellulose dispersion. Place the cellulose dispersion in a reaction vessel equipped with a mechanical stirrer and disperse it for 90 min at 70 °C and a stirring speed of 1000 r / min.
[0087] After dispersion, 17.5 g of phytate interface modifier E was added to the cellulose dispersion, and the mixture was further treated at 70 °C and 1000 r / min for 120 min. Subsequently, 12.5 g of tannic acid was added, and the pH of the system was adjusted to 6.5 using a 5% sodium carbonate aqueous solution. The reaction temperature was then increased to 90 °C, and the reaction was carried out at 1000 r / min for 6 h.
[0088] After the reaction was completed, the reaction system was cooled to 35°C and filtered through a filter cloth to obtain a solid. The obtained solid was washed three times with deionized water and twice with anhydrous ethanol, with each wash using 500 mL of liquid. The washed solid was placed in a forced-air drying oven and dried at 85°C for 10 h to obtain plant polyphenol-phytate synergistic modified cellulose reinforcing component E.
[0089] S3. Weigh 12.5g of indigo dye and 12.5g of hematoxylin dye, add them to a mixed solvent consisting of 150mL of deionized water, 100mL of anhydrous ethanol, 50mL of glycerol, and 100mL of ethyl lactate. Stir at 60℃ and 800r / min for 60min to obtain a plant dye solution. Adjust the pH of the plant dye solution to 7.0 using a 5% (w / w) citric acid aqueous solution.
[0090] 100.0 g of the plant polyphenol-phytate synergistic modified cellulose reinforcing component E was weighed and added to the above plant dye solution. The system temperature was controlled at 85℃, and adsorption treatment was carried out for 5 h at a stirring speed of 800 r / min. After the adsorption treatment, the system was cooled to 30℃, and solid-liquid separation was performed by centrifugation at a speed of 4000 r / min for 10 min. The solid obtained by centrifugation was taken and washed twice with deionized water, with 300 mL of deionized water used each time. The washed solid was placed in a forced-air drying oven and dried at 75℃ for 12 h to obtain the plant dye-loaded modified cellulose reinforcing component E.
[0091] S4. Preparation of premix: Weigh 1000.0g of bio-based PA56 chips with a relative viscosity of 2.8, place them in a vacuum drying oven, and dry them for 8 hours at 105℃ and a vacuum degree of -0.090MPa. Weigh 60.0g of epoxy-modified polyamide elastomer, 15.0g of phosphate ester heat stabilizer, and 10.0g of bio-based fatty acid ester.
[0092] The dried bio-based PA56 chips, epoxy-modified polyamide elastomer, phosphate ester heat stabilizer and bio-based fatty acid ester were added to a high-speed mixer and premixed for 20 minutes at 60°C and 1200 r / min to obtain premix E.
[0093] S5. Preparation of composite chips: Weigh 220.0g of plant dye-loaded modified cellulose reinforcing component E2. Add the premix E through the main feed port of the twin-screw extruder, and add the plant dye-loaded modified cellulose reinforcing component E through the side feed port of the twin-screw extruder.
[0094] The twin-screw extruder has a length-to-diameter ratio of 52:1, a screw speed of 300 r / min, and a vacuum level of -0.090 MPa in the vacuum exhaust section. The temperatures in zones 1, 2, 3, 4, and 5 of the twin-screw extruder are 240℃, 250℃, 260℃, 270℃, and 275℃, respectively, with a die head temperature of 275℃. The melt-blended material is extruded, water-cooled, and pelletized to obtain high-strength bio-based PA56 composite chips E.
[0095] S6. Melt spinning: High-strength bio-based PA56 composite chips E were placed in a vacuum drying oven and dried at 105℃ for 4 hours. The dried high-strength bio-based PA56 composite chips E were then added to a melt spinning apparatus for melt spinning. The spinning temperature was 285℃, the spinneret orifice diameter was 0.45mm, and the number of spinneret orifices was 144.
[0096] The melt is extruded through a spinneret and cooled by side-blowing air at a temperature of 28°C, a relative humidity of 80%, and a wind speed of 0.80 m / s. The nascent fibers are then bundled, oiled, drawn, heat-set, and wound. The oiling rate is 1.2%, the temperature of the first drawing roll is 90°C, the temperature of the second drawing roll is 140°C, the temperature of the heat-setting roll is 170°C, the total draw ratio is 4.5, and the winding speed is 3500 m / min, yielding high-strength bio-based composite fiber E.
[0097] S7. Weaving and Finishing: The high-strength bio-based composite fiber E is fed into a knitting machine to knit into fabric. The knitting structure is plain weave. The resulting fabric is then heat-set at 180℃ for 20 seconds. After heat setting, the high-strength bio-based textile fabric E is obtained.
[0098] Comparative Example 1: Compared with Example 1, the difference is that in steps S4 and S5, the plant dye-loaded modified cellulose reinforcing component A is not added; correspondingly, steps S1, S2, and S3 are omitted, and 1000.0g of bio-based PA56 chips, 30.0g of maleic anhydride-grafted bio-based polyamide, 5.0g of hindered phenolic antioxidant, and 3.0g of polyethylene wax are premixed and then subjected to twin-screw extrusion, melt spinning, drawing, heat setting, weaving, and heat setting treatment to obtain Comparative Example Fabric 1. The remaining steps and process parameters are the same as in Example 1.
[0099] Comparative Example 2: Compared with Example 1, the difference is that phytate interface modifier A was not added in step S2; only tannic acid was used to treat the bacterial cellulose powder. Specifically, 50.0 g of dried bacterial cellulose powder was weighed and added to a water-ethanol mixed solvent consisting of 1050 mL of deionized water and 450 mL of anhydrous ethanol. The mixture was dispersed at 60°C and a stirring speed of 700 r / min for 60 min. Then, 4.0 g of tannic acid was added, and the pH of the system was adjusted to 5.0 using a 5% sodium carbonate aqueous solution. The mixture was then reacted at 70°C and a stirring speed of 700 r / min for 4 h. After subsequent filtration, washing, drying, pulverizing, and sieving, a plant polyphenol-modified cellulose reinforcing component was obtained. In step S3, this plant polyphenol-modified cellulose reinforcing component was used to load madder dye, resulting in a plant dye-loaded plant polyphenol-modified cellulose reinforcing component, which was then used in subsequent steps S4 to S7. The remaining steps and process parameters were the same as in Example 1.
[0100] Comparative Example 3: Compared with Example 1, the difference is that tannic acid was not added in step S2; only phytate interface modifier A was used to treat the bacterial cellulose powder. Specifically, 50.0 g of dried bacterial cellulose powder was weighed and added to a water-ethanol mixed solvent consisting of 1050 mL of deionized water and 450 mL of anhydrous ethanol. The mixture was dispersed at 60°C and a stirring speed of 700 r / min for 60 min. Then, 7.5 g of phytate interface modifier A was added, and the mixture was further treated at 60°C and a stirring speed of 700 r / min for 60 min. The reaction was then carried out at 70°C and a stirring speed of 700 r / min for 4 h. After subsequent filtration, washing, drying, pulverizing, and sieving, a phytate-modified cellulose reinforcing component was obtained. In step S3, this phytate-modified cellulose reinforcing component was used to load madder dye, resulting in a plant dye-loaded phytate-modified cellulose reinforcing component, which was then used in subsequent steps S4 to S7. The remaining steps and process parameters were the same as in Example 1.
[0101] Comparative Example 4: Compared with Example 1, the difference is that the plant dye loading treatment in step S3 is not performed; in step S5, 58.8g of the plant polyphenol-phytate synergistic modified cellulose reinforcing component A is added through the side feed port of the twin-screw extruder, and 1.2g of madder dye is added together with premix A through the main feed port of the twin-screw extruder, so that the total amount of plant polyphenol-phytate synergistic modified cellulose reinforcing component A and madder dye added is 60.0g. The remaining steps and process parameters are the same as in Example 1.
[0102] Comparative Example 5: Compared with Example 2, the difference is that in step S5, the amount of plant dye-loaded modified cellulose reinforcing component B added was adjusted from 140.0 g to 280.0 g. All other raw material types, amounts, and process parameters are the same as in Example 2.
[0103] Comparative Example 6: Compared with Example 2, the difference is that in step S5, the amount of plant dye-loaded modified cellulose reinforcing component B added was adjusted from 140.0 g to 30.0 g. All other raw material types, amounts, and process parameters are the same as in Example 2.
[0104] Performance testing The high-strength bio-based composite fiber AE and high-strength bio-based textile fabric AE prepared in Examples 1-5, as well as the corresponding samples prepared in Comparative Examples 1-6, were used as test objects. Before testing, each test sample was placed in a standard environment at 20°C and 65% relative humidity for 24 hours to equilibrate.
[0105] 1. Fiber breaking strength and elongation at break test The composite fibers obtained by melt spinning in Examples 1-5 and Comparative Examples 1-6 were used as test objects, and the tests were conducted in accordance with GB / T14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments". The sample clamping distance was 250 mm, the tensile speed was 250 mm / min, and the pretension was 0.05 cN / dtex. Each group of samples was tested 10 times, and the average value was taken. The fiber breaking strength is expressed as cN / dtex, and the breaking elongation is expressed as %.
[0106] 2. Fabric breaking strength and tearing strength test Fabrics obtained in Examples 1-5 and Comparative Examples 1-6 were used as test subjects. The breaking strength of the fabrics was tested in accordance with GB / T3923.1-2013 "Textiles - Tensile Properties of Fabrics - Part 1: Determination of Breaking Strength and Elongation at Break - Strip Method". The sample size was 50mm × 300mm, the effective clamping length was 200mm, and the tensile speed was 100mm / min.
[0107] The tear strength of the fabric was tested according to GB / T3917.2-2009 "Textiles - Tear Properties of Fabrics - Part 2: Determination of Tear Strength of Trousers Specimens". The specimen size was 200mm × 50mm, the cut length was 100mm, and the tensile speed was 100mm / min. Woven fabrics were tested 5 times each along the warp and weft directions, and knitted fabrics were tested 5 times each along the longitudinal and transverse directions. The average value was taken.
[0108] 3. Colorfastness test Fabrics obtained in Examples 1-5 and Comparative Examples 2-6 were used as test subjects. The color fastness to washing was tested in accordance with GB / T3921-2008 "Textiles - Tests for color fastness to washing - Color fastness to soaping". The sample size was 40mm × 100mm, the standard soap flake concentration was 5g / L, the liquor ratio was 50:1, the treatment temperature was 40℃, and the treatment time was 30min.
[0109] Color fastness to rubbing was tested according to GB / T3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing". The sample size was 50mm × 140mm, the diameter of the rubbing head was 16mm, the vertical pressure was 9N, and the number of reciprocating rubbing cycles was 10. Color fastness to dry rubbing and color fastness to wet rubbing were tested separately. Comparative Example 1 did not contain plant dye-loaded modified cellulose reinforcing components, and its color fastness was not evaluated.
[0110] 4. Melt processing performance test Composite slices prepared in Examples 1-5 and Comparative Examples 1-6 were used as test objects. The melt flow rate was tested according to GB / T3682.1-2018 "Plastics - Determination of melt mass flow rate and melt volumetric flow rate - Part 1: Standard method". The test temperature was 275℃, the load was 2.16 kg, the preheating time was 300 s, the sample cutting interval was 30 s, and each group of samples was tested three times, with the average value taken.
[0111] Meanwhile, continuous spinning tests were conducted under the melt spinning conditions of the corresponding embodiments or comparative examples. Each group of samples was continuously spun for 2 hours, and the number of yarn breaks that occurred within 2 hours was recorded.
[0112] The test results are shown in Table 1-3 below: Table 1. Test results of mechanical properties of fibers and fabrics
[0113] Table 2 Results of Colorfastness Test
[0114] Table 3 Results of Melt Processing Performance Test
[0115] The results are analyzed as follows: As shown in Table 1, Examples 1-5 used plant polyphenols-phytate synergistic modification of cellulose reinforcing components and preloaded plant dyes onto the plant polyphenols-phytate synergistic modification of cellulose reinforcing components. The resulting samples had higher fiber breaking strength, fabric breaking strength, and fabric tearing strength than the samples without plant dye loading modification of cellulose reinforcing components, without phytate interface modifiers, without plant polyphenols, or without plant dye preloading treatment.
[0116] In particular, compared with Comparative Example 1 (without modified cellulose), the mechanical properties of the fibers and fabrics in all examples were significantly improved, indicating that the synergistic modification of cellulose by plant polyphenols and phytates had a good reinforcing effect. Comparing Example 1 with Comparative Examples 2 and 3, it can be seen that the mechanical properties of phytates or plant polyphenols alone were lower than those of the synergistic modification, demonstrating that phytates (providing interfacial compatibility) and plant polyphenols (providing interfacial reactivity) have a synergistic effect in enhancing the fiber-matrix interface bonding.
[0117] As shown in Table 2, the color fastness to washing, dry rubbing, and wet rubbing of the samples obtained in Examples 1-5 are all higher than those of the samples without phytate interface modifier, without plant polyphenols, or with plant dyes directly added to the melt mixing system. This indicates that the pre-loading treatment of plant dyes and the synergistic modification of cellulose reinforcing components by plant polyphenols and phytate have an impact on color fastness. In other words, the present invention significantly improves the color fastness to washing and rubbing by pre-loading dyes onto modified cellulose, and effectively inhibits dye migration.
[0118] As shown in Table 3, with the increase of the amount of plant dye-loaded modified cellulose reinforcing component added, the melt flow rate of the system decreased, and the tendency for spinning breakage increased. In Comparative Example 5, the addition was too high (28 parts), resulting in an excessively low melt flow rate (9.6 g / 10 min), poor fluidity, and a sharp increase in spinning breakage (11 times), making processing difficult. In Comparative Example 6, the addition was too low (3 parts), resulting in lower fiber breaking strength, fabric breaking strength, and fabric tearing strength compared to Example 2, indicating insufficient mechanical reinforcement and color fixation. These results indicate that the amount of plant dye-loaded modified cellulose reinforcing component added is related to the formation of composite fibers and the mechanical properties of the fabric. Examples 1-5, with addition amounts ranging from 6 to 22 parts, all exhibited good overall performance.
[0119] In summary, this invention, through a specific synergistic modification of cellulose carriers preloading plant dyes, successfully solves the problems of uneven dispersion and migration of plant dyes in the PA56 matrix, thereby improving the mechanical strength of the fabric while ensuring excellent color fastness and good processing performance.
[0120] While specific embodiments of the present invention have been described above, those skilled in the art should understand that the specific embodiments described are merely illustrative and not intended to limit the scope of the present invention. Equivalent modifications and variations made by those skilled in the art in accordance with the spirit of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A high-strength bio-based textile fabric, characterized in that: The high-strength bio-based textile fabric is obtained by weaving or knitting high-strength bio-based composite fibers; the high-strength bio-based composite fibers are prepared from the following raw materials by weight: 100 parts of bio-based PA56, 6-22 parts of modified cellulose reinforcing component loaded with plant dyes, 2-6 parts of bio-based compatibilizer, 0.3-1.5 parts of heat-stabilizing processing aid, and 0.2-1 parts of lubricating and dispersing aid; The modified cellulose reinforcing component loaded with plant dye is a component formed by loading plant dye onto a plant polyphenol-phytate synergistic modified cellulose reinforcing component, wherein the mass ratio of the plant polyphenol-phytate synergistic modified cellulose reinforcing component to the plant dye is 100:2-100:
25. The plant polyphenol-phytate synergistic modified cellulose reinforcing component is prepared from cellulose, phytate interface modifier and plant polyphenols. The amount of phytate interface modifier added is 5%-35% of the mass of cellulose, and the amount of plant polyphenols added is 3%-25% of the mass of cellulose. The phytate interface modifier is prepared by esterification reaction of phytic acid and polyethylene glycol monomethyl ether, wherein the molar ratio of phytic acid to polyethylene glycol monomethyl ether is 1:1 to 1:
4.
2. The high-strength bio-based textile fabric according to claim 1, characterized in that: The relative viscosity of the bio-based PA56 is 2.3-2.8; the cellulose is one or more of bacterial cellulose, microfibrillated cellulose, regenerated cellulose powder, or chopped regenerated cellulose fibers; when the cellulose is in powder form, the particle size of the plant polyphenol-phytate synergistic modified cellulose reinforcing component is 1-80 μm; when the cellulose is chopped regenerated cellulose fiber, the length of the chopped regenerated cellulose fiber is 50-800 μm and the aspect ratio is 5-50.
3. The high-strength bio-based textile fabric according to claim 1, characterized in that: The plant polyphenols are one or more of tannic acid, gallic acid, tea polyphenols, or catechins; the plant dyes are one or more of madder dye, turmeric dye, indigo dye, gallic dye, gardenia yellow dye, or sappanwood dye. The modified cellulose reinforcing component loaded with plant dyes is obtained by adsorption treatment, separation and drying of the plant polyphenol-phytate synergistic modified cellulose reinforcing component in a plant dye solution.
4. The high-strength bio-based textile fabric according to claim 1, characterized in that: The bio-based compatibilizer is one or more of maleic anhydride-grafted bio-based polyamide, maleic anhydride-grafted polyolefin, or epoxy-modified polyamide elastomer; the heat-stabilizing processing aid is one or more of hindered phenolic antioxidants, phosphite antioxidants, or phosphate ester heat stabilizers; the lubricating and dispersing aid is one or more of stearate, polyethylene wax, amide wax, or bio-based fatty acid ester.
5. A method for preparing a high-strength bio-based textile fabric as described in any one of claims 1-4, characterized in that: Includes the following steps: S1. Phytic acid, polyethylene glycol monomethyl ether, and catalyst are subjected to an esterification reaction under nitrogen protection to obtain a phytic acid ester interface modifier; wherein the molar ratio of phytic acid to polyethylene glycol monomethyl ether is 1:1-1:4, the amount of catalyst is 0.2%-2.0% of the total mass of phytic acid and polyethylene glycol monomethyl ether, the esterification reaction temperature is 80-125℃, and the esterification reaction time is 2-8h; S2. Disperse cellulose in a water-ethanol mixed solvent to obtain a cellulose dispersion; add the phytate interface modifier and plant polyphenols to the cellulose dispersion, react at 50-90℃ for 2-6 hours, and after filtration, washing, drying, pulverizing and sieving, obtain the plant polyphenol-phytate synergistic modified cellulose reinforcing component; wherein, the amount of phytate interface modifier added is 5%-35% of the cellulose mass, and the amount of plant polyphenols added is 3%-25% of the cellulose mass; S3. The plant polyphenol-phytate synergistic modified cellulose reinforcing component is added to the plant dye solution and adsorbed at 40-85℃ for 1-5 hours. After separation, washing and drying, the modified cellulose reinforcing component loaded with plant dye is obtained. The mass ratio of the plant polyphenol-phytate synergistic modified cellulose reinforcing component to the plant dye is 100:2-100:
25. S4. Weigh out 100 parts of bio-based PA56, 6-22 parts of the modified cellulose reinforcing component loaded with the plant dye, 2-6 parts of bio-based compatibilizer, 0.3-1.5 parts of heat-stabilizing processing aid, and 0.2-1 parts of lubricating and dispersing aid according to the following mass percentages: premix the bio-based PA56, bio-based compatibilizer, heat-stabilizing processing aid, and lubricating and dispersing aid to obtain a premix. S5. The premixed material is added through the main feed port of the twin-screw extruder, and the modified cellulose reinforcing component loaded with plant dye is added through the side feed port of the twin-screw extruder. After melt mixing, extrusion, cooling, and pelleting, high-strength bio-based PA56 composite chips are obtained. The temperature of the twin-screw extruder is 230-275℃, and the screw speed is 120-300r / min. S6. The high-strength bio-based PA56 composite chips are melt-spun to obtain high-strength bio-based composite fibers; wherein the spinning temperature is 260-285℃ and the total draw ratio is 2.5-4.5 times. S7. The high-strength bio-based composite fiber is woven or knitted and then heat-set to obtain a high-strength bio-based textile fabric; wherein the heat-setting temperature is 120-180℃ and the heat-setting time is 20-120s.
6. The method for preparing high-strength bio-based textile fabric according to claim 5, characterized in that: In step S1, the number average molecular weight of the polyethylene glycol monomethyl ether is 400-5000; the catalyst is one or more of p-toluenesulfonic acid, citric acid, tartaric acid or phosphotungstic acid; the esterification reaction is carried out under a stirring speed of 200-600 r / min, and the water generated in the reaction is removed by depressurization or nitrogen purging.
7. The method for preparing high-strength bio-based textile fabric according to claim 5, characterized in that: In step S2, the volume ratio of water to ethanol in the water-ethanol mixed solvent is 90:10-40:60; the mass concentration of cellulose in the cellulose dispersion is 1%-12%; before adding the phytate interface regulator, the cellulose dispersion is pre-dispersed at 40-70℃ for 20-90 min; after adding the plant polyphenols, the pH of the system is adjusted to 3.5-6.
5.
8. The method for preparing high-strength bio-based textile fabric according to claim 5, characterized in that: In step S3, the mass concentration of the plant dye solution is 0.5%-8%, and the pH is 4.0-7.
0. When the plant dye is a poorly soluble plant dye, an auxiliary solvent is added to the plant dye solution. The auxiliary solvent is one or more of ethanol, glycerol, or ethyl lactate, and the amount of auxiliary solvent used is 5%-40% of the total mass of the plant dye solution.
9. The method for preparing high-strength bio-based textile fabric according to claim 5, characterized in that: In step S4, the premixing temperature is 25-60℃, the premixing speed is 300-1200 r / min, and the premixing time is 5-20 min; In step S5, the length-to-diameter ratio of the twin-screw extruder is 36:1-52:1, and the vacuum degree of the vacuum exhaust section is -0.04MPa to -0.09MPa; the high-strength bio-based PA56 composite chips are dried at 80-105℃ for 4-10h before melt spinning.
10. The method for preparing high-strength bio-based textile fabric according to claim 5, characterized in that: In step S6, the spinneret aperture of the melt spinning process is 0.15-0.45 mm, and the number of spinneret holes is 24-144. After the melt is extruded through the spinneret, it is cooled by side blowing air. The side blowing air temperature is 18-28℃, the side blowing air relative humidity is 55%-80%, and the side blowing air velocity is 0.25-0.80 m / s. The high-strength bio-based composite fiber is bundled, oiled, stretched, heat-set, and wound. The oiling rate is 0.3%-1.2%, the heat-setting roller temperature is 120-170℃, and the winding speed is 800-3500 m / min.